2015
DOI: 10.5551/jat.26906
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis Inhibitor, Endostar, Prevents Vasa Vasorum Neovascularization in a Swine Atherosclerosis Model

Abstract: Aim:Vasa vasorum neovascularization is a key feature of atherosclerosis (AS) and is strongly associated with inflammatory infiltration, lipid deposition, intraplaque hemorrhage, and hemosiderin deposit. Here we investigate the effects of Endostar, a strong anti-angiogenic drug, on vasa vasorum neovascularization in the experimental porcine model of early AS. Methods: Eighteen adult male Ba-Ma mini pigs were randomized into three groups, with six animals in each group. The pigs in the normal (N) group were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 58 publications
(77 reference statements)
1
20
0
Order By: Relevance
“…In preclinical models, it has been demonstrated that pro‐angiogenic strategies augment atherosclerotic plaque growth and vascular inflammation, whereas anti‐angiogenic strategies inhibit atherosclerosis . Previously, we have shown that lesions induced by vein grafting in atherosclerosis‐prone mice display profound plaque neovessels and intraplaque haemorrhage .…”
Section: Introductionmentioning
confidence: 93%
“…In preclinical models, it has been demonstrated that pro‐angiogenic strategies augment atherosclerotic plaque growth and vascular inflammation, whereas anti‐angiogenic strategies inhibit atherosclerosis . Previously, we have shown that lesions induced by vein grafting in atherosclerosis‐prone mice display profound plaque neovessels and intraplaque haemorrhage .…”
Section: Introductionmentioning
confidence: 93%
“…Endostatin, a cleavage product of collagen XVIII, limits angiogenesis through inhibitory interactions with the endothelial integrins α5β1 and αvβ3 [84]. Endostatin treatment limited both plaque angiogenesis and neointimal area in hypercholesterolemic mice [77], and the endostatin-derivative Endostar reduces vasa vasorum density in hypercholesterolemic mini pigs associated with reduced intimal-medial thickness [85]. However, it is not clear from these studies that the reduction in angiogenesis caused the reduction in plaque area, as endostatin may affect other integrin-dependent functions.…”
Section: B Integrins In Endothelial Cell Functionmentioning
confidence: 99%
“…Endothelial dysfunction was a key factor in the progression of atherosclerotic cardiovascular disease [5]. The integrity of endothelial function was closely related to the stable condition of nitric oxide system [6].…”
Section: Introductionmentioning
confidence: 99%